Performance evaluation of wet scrubber system for industrial air pollution control - Danzomo, Bashir Ahmed; Salami, Momoh Jimoh Eyiomika; Jabirin, Sani; Khan, Md. Raisuddin; M. Nor, Iskandar (Asian Research Publishing Network (ARPN), 2012)
The concentration of pollutants emitted from industrial production are generally toxic and hazardous, which can be a serious health risk to humans not limited to respiratory ailments (asthma, bronchitis, tuberculosis, etc) but also to the photosynthesis in plants. In this study, a pilot scrubber system for PM10 control has been designed using data obtained from cement industry. A model for the overall collection efficiency of counter current scrubber system and Langmuir’s approximations were used to predict the performance of the system by considering droplet sizes of 500μm, 1000μm, 1500μm and 2000μm. The range of liquid to gas ratio recommended by the US Environmental Protection Agency (EPA) has been used to investigate the appropriate ratio for optimum performance of the system. Due to reversed flow in the Langmuir’s approximation, negative collection efficiencies for the 1μm dust particle were obtained. For 5μm and 10μm dust particles, the maximum collection efficiencies were determined to be 99.988% and 100.000% at 500μm droplet size and 2.7 l/m3 while the minimum was obtained to be 43.808% and 58.728% at 2000μm droplet size and 0.7 l/m3. The predicted performance of the scrubber system was then validated using the World Health Organization (WHO) air quality standard for PM10.The concentration of pollutants emitted from industrial production are generally toxic and hazardous, which can be a serious health risk to humans not limited to respiratory ailments (asthma, bronchitis, tuberculosis, etc) but also to the photosynthesis in plants. In this study, a pilot scrubber system for PM10 control has been designed using data obtained from cement industry. A model for the overall collection efficiency of counter current scrubber system and Langmuir’s approximations were used to predict the performance of the system by considering droplet sizes of 500μm, 1000μm, 1500μm and 2000μm. The range of liquid to gas ratio recommended by the US Environmental Protection Agency (EPA) has been used to investigate the appropriate ratio for optimum performance of the system. Due to reversed flow in the Langmuir’s approximation, negative collection efficiencies for the 1μm dust particle were obtained. For 5μm and 10μm dust particles, the maximum collection efficiencies were determined to be 99.988% and 100.000% at 500μm droplet size and 2.7 l/m3 while the minimum was obtained to be 43.808% and 58.728% at 2000μm droplet size and 0.7 l/m3. The predicted performance of the scrubber system was then validated using the World Health Organization (WHO) air quality standard for PM10.